Kemampuan Peserta Didik dalam Pengembangan Gerak Tari di Sanggar Stiwang Kabupaten Lampung Barat - Seldatri Hairani; Susi Wendhaningsih; Munaris Munaris (Jurnal Seni dan Pembelajaran, 2017)
The aim of this study was to describe the students ability in developing motion dance in Stiwang gallery west lampung regency. The problem of the research is about how the students ability in the development of motion dance. There are some types of motion given by the trainer, they are ngerujung, humbak moloh, lipeto, ngiau bias, samber melayang. The students learnt the latitude, then they were be able to combine the latitude with the aspect of dancing, which was exploring part of body. After that, the students were able to combine the level aspect. Third, the students were able to use the tempo. The students were able to master and create the aspect of internal latitude and external latitude. Last, the students were able to move the development of motion smoothly, and do not having any difficulty from the aspects above which the students have been developed, so the students will make dancing sequence from a motion to some latitudes.Penelitian bertujuan untuk mendeskripsikan kemampuan peserta didik dalam mengembangkan gerak tari di sanggar Stiwang Kabupaten Lampung Barat. Rumusan masalahnya yakni, bagaimana kemampuan peserta didik dalam pengembangan gerak tari. Ada beberapa ragam gerak yang di berikan oleh pelatih yaitu ngerujung, humbak moloh, lipeto, ngiau bias, samber melayang. Peserta didik belajar ragam gerak kemudian memadukan aspek gerak tari yaitu mengeksplorasi anggota tubuh. Setelah itu, peserta didik memadukan aspek level. Yang ketiga peserta didik mampu menggunakan tempo. Peserta didik mampu menguasai dan menciptakan aspek ruang gerak internal dan ruang gerak ekternal. Yang terakhir adalah peserta didik mampu menggerakkan pengembangan gerak dengan lancar, tidak merasa kesulitan dari aspek-aspek diatas yang sudah peserta didik kembangkan, maka peserta didik akan membuat rangkaian gerak dari satu gerak menjadi beberapa ragam gerak.Kata Kunci: gerak tari, kemampuan peserta didik, pengembangan.